"Targeted Percutaneous Vertebroplasty" Versus Traditional Percutaneous Vertebroplasty for Osteoporotic Vertebral Compression Fracture. (October 2019) - Xu, JunChuan; Lin, JiSheng; Li, Jian; Yang, Yong; Fei, Qi
Objective . In this randomized, nonblinded, controlled study, the feasibility and precision of "targeted percutaneous vertebroplasty" ("targeted PVP") for osteoporotic vertebral compression fracture (OVCF) was evaluated. Methods. A total of 42 patients, aged 50 to 87 years, with OVCF were randomly divided into 2 groups: A and B. Group A underwent "targeted PVP, " and group B underwent traditional PVP with the guidance of C-arm fluoroscopy. Fluoroscopy times for skin puncture points (FTSPP), total radiation doses (TRD), total fluoroscopy times (TFT), and operation time were set as the main evaluation indicators. Results . FTSPP (1.52 ± 0.51 in group A vs 6.62 ± 2.58 in group B, U < .001), TRD (6.26 ± 1.51 in group A vs 11.32 ± 4.21 in group B, P < .001), TFT (16.57 ± 2.79 in group A vs 26.05 ± 6.18 in group B, P < .001), and operation time (20.05 ± 3.38 in group A vs 25.43 ±5.11 in group B, U < .001) were statistically different in the 2 groups. The incidence of cement leakage that occurred in group A (1/21, 4.76%) was significantly less than that in group B (9/21, 42.9%, P < 0.05). Conclusions . "Targeted PVP" may achieve (1) less skin positioning fluoroscopy times, less total fluoroscopy times and dose, shorter operation time, which is more precise than traditional PVP; (2) less incidence of cement leakage; and (3) visualization of the fractured vertebra, which is probably more valuable for the treatment of complicated OVCF patients.